The Impact of Spinning Speed on n-TiO2/ZnO Bilayer Thin Film Fabricated through Sol–Gel Spin-Coating Method - Mohamad Arifin, Nurliyana; Mhd Noor, Ervina Efzan; Mohamad, Fariza; Mohamad, Norhidayah (Mdpi, 2024)
The spinning speed parameter plays a crucial role in determining the properties of an n-TiO2/ZnO bilayer thin film fabricated using the sol–gel spin-coating technique, especially for solar cell applications. In this study, various spinning speeds were employed on an n-TiO2/ZnO bilayer thin film, and characterizations were conducted, such as morphological, structural, and optical properties. The findings revealed that the optimal conditions for the thin film were achieved at a spinning speed of 3000 rpm. Under this condition, a homogenous and compact surface morphology was observed, with an even distribution of ZnO grains. The successful fabrication of an n-TiO2/ZnO bilayer thin film was confirmed by the presence of characteristic peaks for both TiO2 and ZnO. Obviously, three dominant ZnO orientation peaks, which included (100), (002), and (101) were identified. The prevalence of the (002)-ZnO orientation plane indicated a high-quality structure with excellent crystallinity. In terms of optical properties, the achievement of high transmittance up to 75% resembles the high transparency of the thin film. The optical energy of the n-TiO2/ZnO bilayer thin film is estimated at 3.10 eV. In summary, the spinning speed parameter played a pivotal role in enhancing various properties of the thin film, making it a significant factor in its development for diverse applications.